Absenteeism among survivors of the atomic bombing of Hiroshima. Issue 3 (August 1975) - Meigs, J W; Blot, W J; Inoue, S; Meigs, C R
Abstract : Atomic bomb survivors who worked at the Atomic Bomb Casualty Commission in Hiroshima during the years 1968-71 and held handbooks identifying them as survivors took significantly more days of both annual leave and sick leave than did matched and paired control subjects. These differences in leave-taking patterns are considered to be due to behavioural causes as they could not be attributed to radiation dose-response effects.